Do Innovation, Community Participation and Quality of Human Resources Influence the Performance of Village-Owned Enterprise - Akhmad Priharjanto; Nina Andriana (Quantitative Economics and Management Studies, 2023)
This research is a quantitative study that seeks to examine the relationship between innovation, participation and the quality of human resources on the performance of BUM Desa. The research uses primary data collected through questionnaires. The respondents in this research were Village BUM managers in East Java who are members of the East Java BUM Desa Forum. The questionnaire was distributed through the East Java BUM Desa Forum at the end of 2022. The number of respondents who filled out the questionnaire completely was 57 people consisting of the Director, Secretary, Treasurer and BUM Desa Staff. The method used in data processing is SEM PLS. Data is processed with SMART PLS4 application. To ensure the validity and reliability of the model, a model measurement test was carried out using discriminant validity and convergent validity tests. The structural model test was carried out to test the reliability of the model and predict the relationship between exogenous and endogenous variables. The results of the structural model test show that the model used is quite good and can be used to predict relationships between variables and test hypotheses. The results of the hypothesis test show that innovation, participation and quality of resources have a significant positive effect on the performance of BUM Desa.